Thermal testing of new photovoltaic (PV) modules for building integration, encapsulated with glass fibre reinforced composite materials and comparison with conventional Photovoltaic - Agathokleous, Rafaela; Kalogirou, Soteris A. (My University, 2017)
Photovoltaic (PV) panels usage is increased dramatically the last years. The PV panels for building integration however are not so popular yet. This is because the Building Integrated Photovoltaic (BIPV) Systems play an important role on the design of the building. There are architects and designers who like the idea of PV panels integrated on the envelope of a building but there are also those who believe that the colour and shape of the panels eliminate their creativity. BFIRST (Building Integrated Fibre Reinforced Solar Technology) project developed a new solar cells’ encapsulation technology with glass fibre reinforced composite materials, and real size modules are manufactured. The idea behind this technology is to produce rigid photovoltaic panels with shapes that are not flat but they are also light-weight PV modules for building integration. The aim of this study is to compare a ‘BFIRST module’ with a conventional module from the market, in terms of temperature under different amounts of solar radiation and inclination angles. Thus, two experimental apparatuses are constructed to represent building integration, forming an air gap between the PV and a second skin. The purpose of the air gap is to cool the PV panels and avoid the decrease of their efficiency due to overheating. In this study, the ventilation of the air gap is natural without any mechanical means to drive the air. The tests are carried out in the Archimedes Solar Energy Laboratory (ASEL) at Cyprus University of Technology, Limassol, with the use of a large scale solar simulator. Although this is the first time the fibre reinforced encapsulation solar technology is tried, as the modules are produced only for research purposes, the tests show that this technology is very promising and worth to be developed. The maxi-mum temperature recorded was very close with the temperature of the conventional PV panel. The temperature of the BFIRST PV panel under 450 W/m2 constant solar radiation is 57.5ºC while the tem-perature of the conventional PV was 64ºC. For 800 W/m2 constant solar radiation the temperature of the BFIRST PV panel was 73.4ºC and 73.6ºC for the conventional PV panel. An additional test for the BFIRST PV under higher solar radiation is carried out to record highest PV temperature attainable, and the maximum temperature of the panel under 1000 W/m2 was 79ºC at the top side of the panel, which is satisfactory
Keywords: BIPV; Solar simulator; Thermal testing; BFIRST; Photovoltaic